Traditional handloom industry of Kerala - KKN Kurup (Indian Journal of Traditional Knowledge, 2008)
The paper describes the traditional handloom industry of Kerala. The Padma Saliyas community in Kerala used spinning and weaving aspects of textile production. Two sects of caste, Idankai and Valankai represented spinners and weavers, respectively. Native craftsmen of Kerala, produced items like, Mundu, Thorthu, Veshti and Pudava through the handlooms. In Kerala, even now the hand woven clothes known for their durability, finishing, charming colours and smoothness. The traditional pit looms are almost disappeared in favour of wooden framed looms as a matter of technological change. Further from the cottage industry, it has changed into the factory pattern also.